Revenge versus Legality : Wild Justice from Balzac to Clint Eastwood and Abu Ghraib. - Maynard, Katherine (Birkbeck Law Press., 2010)
In the wake of Guantanamo Bay, extraordinary renditions, and secret torture centres in Eastern Europe and elsewhere, this book addresses the relationship between law and wild or vigilante justice - between the power to enforce retribution and the desire to seek revenge.